2009
DOI: 10.1158/1078-0432.ccr-09-2317
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Functional Hyaluronan-CD44 Interactions in CD133-positive Primary Human Ovarian Carcinoma Cells by Small Hyaluronan Oligosaccharides

Abstract: Purpose: CD44 is one of the most common markers used for identification of highly tumorigenic subpopulations of human carcinoma cells, but little is known about the function of CD44 or its major ligand, hyaluronan, in these cells. The purpose of this study was to investigate the involvement of hyaluronan and its interaction with CD44 in the properties of a tumorigenic subpopulation of primary ovarian carcinoma cells. Experimental Design: A tumorigenic subpopulation was identified in ascites fluids from ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 47 publications
8
94
0
Order By: Relevance
“…Therefore, targeting such antigens with mAbs or small molecules also may affect the normal tissues that express these antigens (48,49). However, with few exceptions (50), the postpartum expression of ROR1 seems restricted to cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, targeting such antigens with mAbs or small molecules also may affect the normal tissues that express these antigens (48,49). However, with few exceptions (50), the postpartum expression of ROR1 seems restricted to cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…CD44, a specific receptor for hyaluronic acid and adhesion/homing molecule (Naor et al, 2008;Jaggupilli and Elkord, 2012), is a multifunctional class I transmembrane glycoprotein expressed in almost all normal and cancer cells (Naor et al, 2008;Jaggupilli and Elkord, 2012). In several previous studies, CD44 individually or in combination with other putative CSC markers has been applied to isolate CSCs in various solid tumors including breast (Al-Hajj et al, 2003), prostate, pancreas (Immervoll et al, 2011), ovarian, colorectal (Wielenga et al, 1993;Woodman et al, 1996;Choi et al, 2009), head and neck (Satpute et al, 2013) and bladder cancers (Yang and Chang, 2008;Chan et al, 2009;Slomiany et al, 2009;Lee et al, 2010;Su et al, 2010;Jaggupilli and Elkord, 2012). Both in vitro and in vivo studies have shown that CD44+ bladder cancer cells have higher tumorigenic potential compared to CD44-bladder cancer cells; whereas they have lower tumorigenic potential compared to ALDH1A1+ cells .…”
Section: Introductionmentioning
confidence: 99%
“…To determine the involvement of CD44 in MM-BMSC interactions, adhesion assays were also performed in the presence of either an anti-CD44 ab (hermes-1) (Thermo Scientific) or hyaluronan oligosaccharides (o-HA) (100 g/ml). Hyaluronan oligosaccharides used in this study were a mixed fraction, with the average molecular weight of 2.5 ϫ 10 3 , composed of 2-10 disaccharide units that were fractionated from testicular hyaluronidase (Sigma, type 1-S) digests of hyaluronan polymer (Sigma, sodium salt), as described previously (20). For adhesion to collagen I, wells coated with collagen I were blocked with 1% BSA in serum-free culture medium for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…These results clearly demonstrate the role of serglycin in mediating myeloma cell adhesion and further confirm that the decreased adhesion shown by serglycin knockdown cells is not an artifact of knockdown. To determine if CD44 is involved in this adhesion mechanism, the adhesion of MM cells to BMSCs was examined in the presence of antagonists of CD44-ligand interaction, either hyaluronan oligosaccharides (o-HA) (20,27) or anti-CD44 monoclonal antibodies (hermes-1). As shown in Fig.…”
Section: Serglycin Promotes Myeloma Cell Adhesion To Bone Marrowmentioning
confidence: 99%